The Suitable Model of Online Learning and Teaching for Ubon Ratchathani Rajabhat University - บรรลือ สุวัฒน์ (Journal of Roi Et Rajabhat University, 2017)
The aims of this research were to 1) develop the suitable model of online learning and teaching for Ubon Ratchathani Rajabhat University and 2) explore the effectiveness of the developed model of online learning and teaching. The three steps of research methodology world as follows : The first step was to study the needs of teachers and students of Ubon Ratchathani Rajabhat University in an online learning and teaching model in order to analyze and synthesize the framework of online learning and teaching development. The second step was to develop the suitable online learning and teaching model.And the last was to examine the effectiveness of the developed online learning and teaching model. The samples were 1) 80 of teachers and students of Ubon Ratchathani Rajabhat University, 2) 3 experts in designing online learning and teaching, and 3) 84 of students of Computer Science Faculty those registered for Storage and Retrieval of Information course. The research tools were 1) the questionnaire 2) the assessment form for the expert 3) the prototype of online learning and teaching and 4) the learning achievement test and t-test statistics. The research results found that: 1. Three steps of the online learning and teaching model for Ubon Ratchathani Rajabhat University 1) Pre-Leaning step consists 1.1) student analysis and 1.2) content analysis, 2) During-Learning step consists 2.1) orientation course and 2.2) Learning and Teaching management, and 3) Evaluation process. 2. Developmental testing of an online learning and teaching model found that the statistically insignificant at level of .05 between developed online learning and normal classroom. Thus, online learning is effective as a normal classroom.